TAKING CARE OF THE SICK ELDER PEOPLE AT HOME IN THE SPEECH OF FAMILIAL CARE TAKER - Roceli Brum Cattani; Nara Marilene Oliveira Girardon-Perlini (Universidade Federal de Goias, 2004)
This investigation is about an exploratory, descriptive and in a qualitative approach study, which hadas its objective to know how the choice of the sick elderly peoples familial caretaker occurs and how the caretakerfeels in this role. The main caretaker was interviewed in home visits. The sample was constituted of nine familialcaretakers, mainly from the female sex: wives, daughters, daughters-in-law, granddaughters, and the husband. Forthe analysis of the data, the content analysis, following the methodological steps of Minayo, was used. Twoanalytical categories were elaborated: being a familial caretaker: is it an option or an obligation?, which shows thatthe choice of taking care is closely related to the feeling of obligation, but also to affection relations, gratitude andthe impossibility of choosing another caretaker, and being a sick elderly peoples familial caretaker that approachesfeelings of gratitude, resignation, inexperience in face of the care demands, physical and emotional tiredness, lossof freedom and solitude due to the activity in the caretaker.